2020
DOI: 10.1038/s41598-020-57566-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic impacts of chronic unpredictable mild stress on metabolomics in rats

Abstract: Depression is the most common disabling psychiatric disease, with a high prevalence and mortality. Chronic unpredictable mild stress (CUMS) is a well-accepted method used to mimic clinical depression. Recent evidence has consistently suggested that the cumulative effects of CUMS could lead to allostatic overload in the body, thereby inducing systemic disorders; however, there are no previous systematic metabonomics studies on the main stress-targeted tissues associated with depression. A non-targeted gas chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Additionally, pyruvic acid and 3-hydroxibutiric acid in plasma metabolomics and N,N-dimethylglycine and taurine in urine metabolomics match as candidate biomarkers in two different statistical methodologies (Figure 7). Globally, considering the results of the present 3d CUMS study and previous CUMS studies, we have observed that energy metabolism has a greater impact together with fatty acids, while in CUMS, energy metabolism does not have much impact while there is greater alteration of amino acids associated with the monitoring of depression [31,52].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Additionally, pyruvic acid and 3-hydroxibutiric acid in plasma metabolomics and N,N-dimethylglycine and taurine in urine metabolomics match as candidate biomarkers in two different statistical methodologies (Figure 7). Globally, considering the results of the present 3d CUMS study and previous CUMS studies, we have observed that energy metabolism has a greater impact together with fatty acids, while in CUMS, energy metabolism does not have much impact while there is greater alteration of amino acids associated with the monitoring of depression [31,52].…”
Section: Discussionsupporting
confidence: 68%
“…Related to the energy metabolism, pyruvic acid, which is increased in the 3 CUMS group, is the end-product of glycolysis, a major substrate for oxidative metabolism and a branching point for glucose, lactate, fatty acid and amino acid synthesis [30]. In previous CUMS studies, pyruvic acid was disturbed without being significant, and for this reason, we suggest that the increased pyruvic acid is related to the early response to stress instead of depression when pyruvic acid returns to its normal levels, leading to other metabolic changes [31]. The slightly plasmatic increase in 3-hydroxybutiric acid, a known ketone body, reflects an increase in energy production through fatty acid oxidation, supporting the idea that the disruption of carbohydrate and energy metabolism might be disrupted in the 3d CUMS group.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Accumulated evidence has revealed the link between CMS and alteration of metabolism. For example, stressed animals demonstrate decreased food intake and preference, as well as decreased appetite hormone homeostasis and systematic metabolome changes [ 31 , 32 ]. Upon deeper examination, we found significant changes in gene families related to electron transfer in the mitochondria complexes of stressed mice, suggesting that energy consumption may be affected by CMS ( Figure 4 d,e).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas acute stress is often investigated in preclinical rodent studies, the extended duration of the chronic unpredictable stress paradigm in this study provided an opportunity to investigate the effects of PB supplements in chronically challenged animals. Since past research suggests that the effects of PB-supplemented diets are most influential in stressful conditions ( Papalini et al, 2018 ), the animals in this study were exposed to chronic unpredictable stress ( Kent et al, 2018 ), as this is a preclinical model with putative translational value for human stress-related illnesses including depression ( Geng et al, 2020 , Hariri and Holmes, 2015 , Nikolova et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%